ANALISIS FAKTOR PENENTU MINAT MASYARAKAT BERDONASI PADA GERAKAN INFAQ BERAS ACEH - Muhammad Yasir; Irwandi Irwandi (SYARIAH: Journal of Islamic Law, 2023)
This study aims to determine the effect of Religiosity, Income, and Situational Altruism simultaneously and partially on Community Interest in Donating at Gerakan Infaq Beras Aceh. Based on 100 questionnaires distributed to respondents, using the Probability Sampling method as measured by the Purposive Sampling technique and analyzed using multiple linear regression models, the results showed that together all the variables in this study had a positive and significant effect on Interest in Donating. Then partially the variables of Reliability, Income, and Situational Altruism have a positive and significant effect on Interest in Donating at Gerakan Infaq Beras Aceh. Promotional activities still really need to be improved considering that there are still many people who do not know about this philanthropy so that Gerakan Infaq Beras Aceh can become a great humanitarian platform and more and more people are interested in donating.